Single stage arthroscopically assisted reconstruction of Multiligamentous Knee Injury with autografts. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of single stage arthroscopically assisted reconstruction of multiligamentous knee injury (MLKI) with autografts.Methods: This descriptive study was conducted in Orthopaedic Department Liaquat National Hospital and Medical College Karachi from 21st January 2017 to 21st January 2022.All adults’ patients with multiligamentous knee injury (MLKI) fulfilling the inclusion criteria were treated with arthroscopically assisted single stage surgery utilizing Hamstring and Quadriceps tendon autografts. Post operative functional outcome was assessed with International Knee Documentation Committee scores (IKDC) and Tegner-Lysholm score at six months, one year and two years follow up. The pre surgery and post-surgery IKDC and Tegner-Lysholm scores were compared and P value was calculated with paired sample-t test. P value